Acceptance of IIUM.FM by Human Sciences undergraduate students - Lahabou , Mahaman; Wok, Saodah (2011)
This study investigates Human Sciences (HS) students’ acceptance of IIUM.FM, their newly established online campus radio, by using Technology Acceptance Model (TAM) as the theoretical background. An external variable, knowledge, was added to the original model. The objectives of this study are to (1) find out the patterns of listening among students, (2) determine the knowledge about IIUM.FM among students, (3) find out the perceived usefulness of listening to IIUM.FM among students, (4) find out the attitude of students towards listening to IIUM.FM, and (5) analyze the relationship between knowledge about IIUM.FM, the perceived usefulness of listening, attitude towards listening and actual listening to IIUM.FM. A cross-sectional survey design was employed to gather data through a self-administered questionnaire to a sample of 238 undergraduate students to test three hypotheses generated from literature related to TAM. The findings showed that listeners are highly knowledgeable about IIUM.FM, have positive perception of the usefulness of listening to the radio as well as a positive attitude towards listening to it. Knowledge about IIUM.FM was found to have an influence on actual listening directly and indirectly via Perceived Usefulness of Listening (PUOL) and attitude towards listening.